Amyand's Hernia. A Case Report - Raysy Sardiñas Ponce; Leonel Hernández Torres; José Miguel Pinza Jojoa (Medisur)
Presence of the vermiform appendix in an inguinal hernia sac, with or without appendicitis, is called Amyand's hernia. It occurs in approximately 1% of inguinal hernia patients. It is more common in men and is frequently found on the right side due to the location of the appendix. Clinically, it presents as a complicated inguinal hernia causing symptoms such as fever or signs of mechanical intestinal obstruction, depending on the state of the appendix. The latter determines the type of surgical approach and hernia repair. The third Amyand's hernia case treated at the Enrique Cabrera Hospital is presented. The patient underwent an appendectomy and inguinal hernia repair with satisfactory outcomes